Loss of retinal ganglion cells in a new genetic mouse model for primary open‐angle glaucoma. Issue 8 (29th May 2019) - Reinehr, Sabrina; Koch, Dennis; Weiss, Maximilian; Froemel, Franziska; Voss, Christina; Dick, H. Burkhard; Fuchshofer, Rudolf; Joachim, Stephanie C.
Abstract: Primary open‐angle glaucoma (POAG) is one of the most common causes for blindness worldwide. Although an elevated intraocular pressure (IOP) is the main risk factor, the exact pathology remained indistinguishable. Therefore, it is necessary to have appropriate models to investigate these mechanisms. Here, we analysed a transgenic glaucoma mouse model (βB1‐CTGF) to elucidate new possible mechanisms of the disease. Therefore, IOP was measured in βB1‐CTGF and wildtype mice at 5, 10 and 15 weeks of age. At 5 and 10 weeks, the IOP in both groups were comparable ( P > 0.05). After 15 weeks, a significant elevated IOP was measured in βB1‐CTGF mice ( P < 0.001). At 15 weeks, electroretinogram measurements were performed and both the a‐ and b‐wave amplitudes were significantly decreased in βB1‐CTGF retinae (both P < 0.01). Significantly fewer Brn‐3a + retinal ganglion cells (RGCs) were observed in the βB1‐CTGF group on flatmounts ( P = 0.02), cross‐sections ( P < 0.001) and also via quantitative real‐time PCR ( P = 0.02). Additionally, significantly more cleaved caspase 3 + RGCs were seen in the βB1‐CTGF group ( P = 0.002). Furthermore, a decrease in recoverin + cells was observable in the βB1‐CTGF animals ( P = 0.004). Accordingly, a significant down‐regulation of Recoverin mRNA levels were noted ( P < 0.001). Gfap expression, on the other hand, was higher in βB1‐CTGF retinae ( P = 0.023). Additionally, more glutamine synthetase signal was noted ( P = 0.04). Although no alterations were observed regarding photoreceptors via immunohistology, a significant decrease of Rhodopsin ( P = 0.003) and Opsin mRNA ( P = 0.03) was noted. We therefore assume that the βB1‐CTGF mouse could serve as an excellent model for better understanding the pathomechanisms in POAG.